Tantangan Peningkatan Kualitas dan Profesionalisme Guru dalam Pengembangan Pendidikan Islam di Indonesia - Sukari; Hudallah (An-naba : Jurnal Pendidikan dan Pengabdian Masyarakat, 2026)
Islamic education in Indonesia faces increasingly complex challenges along with the development of science, technology, and social transformation. One of the key factors determining the success of Islamic education development is the quality and professionalism of teachers as the main actors in the educational process. This study aims to analyze the challenges in improving the quality and professionalism of Islamic education teachers in Indonesia and to identify strategic efforts for strengthening teacher competencies in responding to the demands of modern education. This study employs a qualitative approach using a library research method through the analysis of relevant academic literature and educational policy documents, including regulations, scholarly books, and scientific journal articles. The data were analyzed using content analysis techniques to identify the conditions, challenges, and strategies related to the professional development of Islamic education teachers. The findings reveal that the quality and professionalism of Islamic education teachers have improved through various competency development programs; however, several challenges remain in strengthening professional, pedagogical, personal, and social competencies. The major challenges include limited instructional innovation, insufficient digital literacy, the need to develop a research culture among teachers, and the strengthening of teachers’ exemplary roles and social competencies. Therefore, strategies to enhance the quality of Islamic education require continuous professional development, improvement of digital literacy, pedagogical innovation, strengthening of professional learning communities, and character development of teachers as Islamic educators. This study highlights that teacher professionalism is a crucial factor in establishing Islamic education that is adaptive, high-quality, and capable of responding to the demands of contemporary society. Keywords: Islamic education, teacher professionalism, teacher competence, educational quality, teacher development   Abstrak Pendidikan Islam di Indonesia menghadapi tantangan yang semakin kompleks seiring dengan perkembangan ilmu pengetahuan, teknologi, dan perubahan sosial masyarakat. Salah satu faktor utama yang menentukan keberhasilan pengembangan pendidikan Islam adalah kualitas dan profesionalisme guru sebagai pelaksana utama proses pendidikan. Penelitian ini bertujuan untuk menganalisis tantangan peningkatan kualitas dan profesionalisme guru dalam pengembangan pendidikan Islam di Indonesia serta mengidentifikasi strategi penguatan kompetensi guru dalam menghadapi tuntutan pendidikan modern. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kepustakaan (library research) melalui analisis berbagai literatur akademik dan dokumen kebijakan yang relevan, seperti regulasi pendidikan, buku ilmiah, dan artikel jurnal. Data dianalisis menggunakan teknik analisis isi (content analysis) untuk mengidentifikasi kondisi, tantangan, dan strategi pengembangan profesionalisme guru pendidikan Islam. Hasil penelitian menunjukkan bahwa kualitas dan profesionalisme guru pendidikan Islam telah mengalami perkembangan melalui berbagai program peningkatan kompetensi, namun masih menghadapi tantangan dalam aspek kompetensi profesional, pedagogik, kepribadian, dan sosial. Tantangan utama meliputi keterbatasan inovasi pembelajaran, pemanfaatan teknologi digital, pengembangan budaya penelitian, serta penguatan keteladanan dan kemampuan sosial guru. Strategi yang diperlukan untuk memperkuat mutu pendidikan Islam meliputi pengembangan profesional berkelanjutan, peningkatan literasi digital, inovasi pedagogik, penguatan komunitas profesi, serta pembinaan karakter guru sebagai pendidik Islam. Kajian ini menegaskan bahwa profesionalisme guru menjadi faktor kunci dalam mewujudkan pendidikan Islam yang adaptif, berkualitas, dan mampu menjawab kebutuhan masyarakat modern. Kata kunci: pendidikan Islam, profesionalisme guru, kompetensi guru, kualitas pendidikan, pengembangan guru.